Nilai-Nilai Transformasi Sosial Dalam Pemikiran Teologi Muhammad Fethullah Gulen - Lukman Hakim (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
Theological study has focused more on the theoretical and conceptual aspects. Thus, it is unable to answer various problems faced by the ummah and is unable to actualize social transformation. This paper aims to learn the values of social transformation in the theological thoughts of Muhammad Fethullah Gulen. The study findings revealed some values in the social transformation of his theological thoughts. First, He places human beings as an activator agent and viewed as a dynamic figure who embodies the role of social transformation. Second, a theological construct that puts human freedom and God's will in balance. This theology model provides an opportunity for humans to determine their own transformation but still accept God as the one who determines the results. Third, the notion of work ethic. Gulen suggests that to establish a social transformation, Muslims should be passionate, determinant, patient, aspirated, and courageous to spread goodness in the community. He offered this theological idea to encourage human beings to achieve a social transformation for future better and dignified Islam.